Evaluación de riesgo de desastre por inundación del centro poblado de San José de Habana - Habana, 2012 - Pilco Izquierdo, Geidy Carmin (2012)
The present thesis project "Risk disaster evaluation for flood of the Filled Center San Jose de Habana – Habana, 2012”. It performs vital importance to develop it, to anticipate disasters that could affect both the people and the environment, thus altering the quality and the living standard of the populated center, having as principal aim evaluate the risks of disaster for flood of the filled center Habana San Jose. A work of validation was realized in field, through the referencing and taking pictures of the potential dangers or threats by flood, identified in the working meeting, dangers or threats that could affect not only the crops, homes but also the investment in basic infrastructure and human lives in a possible occurrence of a disaster In this sense the study, it is vital because through it you can generate planning alternatives, educational and, awareness with the local population, in order to prevent the flooding areas identified in the future causing greater damage and losses. In addition, the present study will guide the work of the technical municipal, local facilitators, trainers, educational, professionals interested in the topic and other people in order to propose alternatives to reduce vulnerability and to increase the safety levels of the population of the populated center. At the conclusion of the present study it was found that the Habana San Jose town has high, average and low irrigation; presents alternatives or measures to reduce damage or loss, with the aim of achieving greater sustainability of investments in the SNIP that is achieved through a coordinated planning in different levels: local, regional and national. This involves the participation of all stakeholders of the Habana district, to promote a better understanding of the risks and flooding dangers, as well as distinguish the vulnerabilities of the needs and assess the social and organizational capabilities in each of the levels. Key words: reduce vulnerability, reduce damage.